Unexpected finding of the invasive Baikalian amphipod Gmelinoides fasciatus in a cold spring of the southern Pamir Mountains - Sidorov, D. A.; Gontcharov, A. A.; Palatov, D. M. (Knowledge and Management of Aquatic Ecosystems (2013) 411, 2013)
A specimen of the Baikalian micruropodid amphipod Gmelinoides fasciatus was recently found in a spring brook in the Shugnansky District, Gorno-Badakhshan Autonomous Province of Tajikistan. This occurrence represents the first record confirmed with mt-cox1 sequence data for this species from the Pamir Mountains. Reliable information on the introduction of Gm. fasciatus and the pattern of its distribution in the region is not yet available, but we hypothesise that the species was introduced intentionally to increase the fish productivity of Yashilkul Lake in 1973-1974. This finding of probably an isolated population shifts the southernmost limit of the species range approximately 1400 km from the Bukhtarminskoye reservoir, Eastern Kazakhstan. A general overview of the morphology, ecology, distribution and invasive history of the species is provided.